EFFECT OF PACKAGING MATERIAL AND DARK STORAGE ON THE POSTHARVEST QUALITY AND SHELF LIFE OF NAVEL ORANGES (Citrus sinensis L., Osbeck) - Mohamed Ibrahim Elsayed (Journal of Animal and Plant Sciences, 2026)
Despite having a stiff peel, oranges suffer from many internal physiological changes and pathological damage during the postharvest stage. Oranges have a limited postharvest shelf life at ambient conditions. Storage conditions and Packaging materials are crucial factors in extending shelf life and maintaining fruit quality. In the current study, Washington Navel oranges were employed to assess the storage of fruit in negative modified atmosphere conditions with lower O2 and higher CO2 created by different methods of packing such as perforated low-density polyethylene (LDPE), perforated polyethylene low density high molecular weight (LDHM) and perforated cardboard boxes (CB) and control fruits with no packing (NP) on fruit properties. All treatments were split into two sections that were stored in complete darkness and those that were stored under conditions of light at 23°C and 85% relative humidity for 20 days. The treatments were arranged in a completely randomized design (CRD) under factorial arrangement, and the whole experiment was replicated three times. Storage properties were assessed, and CD+LDHM treatment produced the best in maintaining weight loss (1.30%) and the least in fruit firmness change (41.36 N), TSS (11.36 Brix), total acidity (0.98%), and vitamin C (25.19 mg/100ml). It was followed closely by CD+LDPE treatment. On the other hand, the unpacked fruit had the highest weight loss and chemical or physical property changes, either under complete darkness or light conditions. The results indicated that This study demonstrated that modified atmosphere using perforated LDPE and LDMH packaging significantly improved the postharvest quality, extended the shelf life of Navel oranges, and reduced deterioration compared to carton boxes or unpackaged as a control.
Keywords: orange; postharvest; packaging; plastic materials; darkness; storage; shelf life; quality; enzymes